2008
DOI: 10.1038/mp.2008.28
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cortical muscarinic receptors define a subgroup of subjects with schizophrenia

Abstract: Schizophrenia is widely acknowledged as being a syndrome, consisting of an undefined number of diseases probably with differing pathologies. Although studying a syndrome makes the identification of an underlying pathology more difficult; neuroimaging, neuropsychopharmacological and post-mortem brain studies all implicate muscarinic acetylcholine receptors (CHRM) in the pathology of the disorder. We have established that the CHRM1 is selectively decreased in the dorsolateral prefrontal cortex of subjects with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 36 publications
5
132
2
Order By: Relevance
“…Taken together with previous clinical studies in schizophrenia patients and preclinical studies in rodent models, these data form a strong argument for the functional relevance of muscarinic plasticity in schizophreniarelated behavioral deficits and support the hypothesis that highly selective M 1 PAMs may provide therapeutic efficacy in treatment of some aspects of the negative and cognitive symptoms in schizophrenia patients. The present findings are especially interesting in light of multiple previous studies that cholinergic signaling Role of M 1 PAM in PCP-treated mice A Ghoshal et al is disrupted in the PFC and other cortical and limbic forebrain regions of schizophrenia patients (Berman et al, 2007;Dean et al, 2002;Raedler et al, 2007;Scarr et al, 2009a;Zavitsanou et al, 2004). Of particular interest is the recent finding that a defined subset of schizophrenia patients display decreases in M 1 levels in PFC and other cortical and forebrain regions (Dean et al, 2002;Gibbons et al, 2013).…”
Section: Role Of M 1 Pam In Pcp-treated Micementioning
confidence: 70%
“…Taken together with previous clinical studies in schizophrenia patients and preclinical studies in rodent models, these data form a strong argument for the functional relevance of muscarinic plasticity in schizophreniarelated behavioral deficits and support the hypothesis that highly selective M 1 PAMs may provide therapeutic efficacy in treatment of some aspects of the negative and cognitive symptoms in schizophrenia patients. The present findings are especially interesting in light of multiple previous studies that cholinergic signaling Role of M 1 PAM in PCP-treated mice A Ghoshal et al is disrupted in the PFC and other cortical and limbic forebrain regions of schizophrenia patients (Berman et al, 2007;Dean et al, 2002;Raedler et al, 2007;Scarr et al, 2009a;Zavitsanou et al, 2004). Of particular interest is the recent finding that a defined subset of schizophrenia patients display decreases in M 1 levels in PFC and other cortical and forebrain regions (Dean et al, 2002;Gibbons et al, 2013).…”
Section: Role Of M 1 Pam In Pcp-treated Micementioning
confidence: 70%
“…ACh plays a critical role in cognitive processing, and its actions are mediated in part through muscarinic M1 receptors. One study reported that, in 26% of patients with schizophrenia, muscarinic M1 receptor levels were reduced by 74% in the PFC (Scarr et al, 2009). Because 5-HT 4 receptor levels are reportedly unchanged in schizophrenia (Dean et al, 1999), 5-HT 4 receptor agonists might help to restore M1 receptor-mediated neurotransmission by increasing cortical ACh levels.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been shown that the decrease in cortical M1 receptors is restricted to a subgroup of patients within the syndrome of schizophrenia [37]. The subgroup comprises approximately 25% of the subjects with schizophrenia, who have, on average, 75% lower M1 receptors than either control subjects or other subjects with schizophrenia (See Figure 1).…”
Section: Muscarinic Receptors and Schizophreniamentioning
confidence: 99%
“…A specific single nucleotide polymorphism (SNP) in the M1 receptor has been associated with altered performance on measures for executive function in people with schizophrenia [35], however, to date, there have been no associations between any M1 SNPs and the disorder itself [35][36][37]. Variations in the M5 receptor have been associated with schizophrenia but only when they occur in combination with changes in the sequence of the alpha 7 nicotinic receptor (CHRNA7) [38] suggesting that changes in both receptors may contribute to the symptoms of the disorder.…”
Section: Muscarinic Receptors and Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation